Long-term Exposure to Fine Particulate Matter Air Pollution and Mortality Among Canadian Women. Issue 4 (July 2015) - Villeneuve, Paul J.; Weichenthal, Scott A.; Crouse, Daniel; Miller, Anthony B.; To, Teresa; Martin, Randall V.; van Donkelaar, Aaron; Wall, Claus; Burnett, Richard T.
<x xml:space="preserve">Abstract</x> Background: Long-term exposure to fine particulate matter (PM2.5) has been associated with increased mortality, especially from cardiovascular disease. There are, however, uncertainties about the nature of the exposure–response relation at lower concentrations. In Canada, where ambient air pollution levels are substantially lower than in most other countries, there have been few attempts to study associations between long-term exposure to PM2.5 and mortality. Methods: We present a prospective cohort analysis of 89, 248 women who enrolled in the Canadian National Breast Screening Study between 1980 and 1985, and for whom residential measures of PM2.5 could be assigned. We derived individual-level estimates of long-term exposure to PM2.5 from satellite observations. We linked cohort records to national mortality data to ascertain mortality between 1980 and 2005. We used Cox proportional hazards models to characterize associations between PM2.5 and several causes of death. The hazard ratios (HRs) and 95% confidence intervals (CIs) computed from these models were adjusted for several individual and neighborhood-level characteristics. Results: The cohort was composed predominantly of Canadian-born (82%) and married (80%) women. The median residential concentration of PM2.5 was 9.1 μg/m3 (standard deviation = 3.4). In fully adjusted models, a 10 μg/m3 increase in PM2.5 exposure was associated with elevated risks of nonaccidental (HR: 1.12; 95% CI = 1.04, 1.19), and ischemic heart disease mortality (HR: 1.34; 95% CI = 1.09, 1.66). Conclusions: The findings from this study provide additional support for the hypothesis that exposure to very low levels of ambient PM2.5 increases the risk of cardiovascular mortality.